Knowledge of oral and oropharyngeal cancer by dental surgeons: an integrative review - Andrea Tatiane Oliveira da Silva Barros; Clayton Clenisson de Carvalho Silva; Vanessa de Carla Batista dos Santos; Camila Maria Beder Ribeiro Girish Panjwani; Kevan Guilherme Nóbrega Barbosa; Sonia Maria Soares Ferreira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify the evidence available in the literature on the knowledge of dentists regarding risk factors and early diagnosis of oral and oropharyngeal cancer. Methods: it is an integrative review of the literature. Boolean descriptors and operators were searched in the PubMed and LILACS databases, using gray literature, in English, Spanish and Portuguese. Results: of the 79 PubMed and 152 LILACS articles, 24 were selected. Of these, eight showed good knowledge of dentists, while most showed low or little knowledge of risk factors and early diagnosis in dentists. All studies, however, highlight the need for continuing education to improve and maintain knowledge about risk factors and early diagnosis. Conclusions: most dental surgeons have insufficient knowledge of oral/oropharyngeal cancer. Continued education is suggested, aiming at improving knowledge and early diagnosis.